KOMUNIKASI POLITIK DAN POLITIK MEDIA MASSA DI INDONESIA - Fachrur Rizha (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
This article explains how the mass media become a means of political communication in Indonesia. In communication process, it needs channels (media channel) to convey a message that aims to influence the communicant to what the communicator wants. The mass media is a political campaign tool that is considered quite effective in influencing attitudes and behavior public. So that a number of national political elites take part in establishment and ownership of a number of mass media companies in Indonesia. This will certainly impact on the credibility and media function in democracy which makes the mass media considered to no longer play an important role in guarding the democratic process. However this only becomes a campaign tool for positive imaging of candidates and political groups in the election process.